Problemy realizacji „Krajowego programu zwiększania lesistości” po wstąpieniu Polski do Unii Europejskiej - Kaliszewski, Adam (Leśne Prace Badawcze, 2012)
The status of the „National Program for Expanding of Forest Cover” (KPZL) and its implementation during the period 2001–2010 are presented, along with the results of a survey on the major barriers to the Program’s execution following Poland’s accession to the European Union in 2004. The study is based on official statistical data and a questionnaire survey carried out in randomly-selected local public authorities all over the country. From the beginning of the 1990s, the area of agricultural lands afforested annually successively increased, until it reached its a peak in 2003 (26.5 thousand ha). Since 2004, however, the annual rate of afforestation rapidly decreased, and dropping to 5.6 thousand ha in 2009, and 5.9 thousand ha in 2010. Over the last decade, altogether 145.1 thousand ha of agricultural lands were afforested, which amounted to 52% of the target defined in the KPZL. During the period 2006–2010 only 49.7 thousand ha of agricultural lands were afforested and the rate of implementation of the program hardly exceeded 30%. The program has also been very unevenly adopted around the country. There have been too few new forests established in areas of the acute afforestation, i.e. in central and southern parts of the country. The most important obstacles for implementation of the „National Program for Expanding of Forest Cover” following Poland’s accession to the European Union stem from: – high competitiveness of direct payments for agricultural production compared to the afforestation premium, as well as complicated procedures for granting financial support, – the enlargement of minimal plot areas supported by the afforestation premium from 0.1 ha to 0.3 ha in 2004 and up to 0.5 ha in 2007, – the exclusion of permanent grasslands from afforestation, – a lack of financial support for afforestation of land within Natura 2000 areas which are not yet covered by protection plans, – a lack of promotion of financial support for afforestation among farmers and lack of training for its implementation, – a lack of up-to-date local spatial management plans. The study shows that the current rate of afforestation is insufficient to reach the target defined in the KPZL (30% of the country’s land-area covered by forests by 2020). The breakdown in program implementation seems to be an unexpected outcome of Poland’s accession to the EU resulting from the ongoing economic and social transformation of rural areas. The main factors influencing its lack of uptake appear to be long-term, thus it is rather unlikely that the unfavorable trends in the rate of afforestation may become reversed in the coming years.